Spirituality, quality of life, psychological adjustment in terminal cancer patients in hospice. (27th July 2015) - Bovero, A.; Leombruni, P.; Miniotti, M.; Rocca, G.; Torta, R.
Abstract : The purpose of this study was to show the different components of spirituality in the last few weeks of life for advanced cancer patients admitted to hospice and to evaluate quality of life (QoL), pain, anxiety, depression and psychological adjustment to cancer. One hundred and fifteen patients were interviewed with a series of rating scales: the Functional Assessment of Chronic Illness Therapy – Spiritual Well‐Being Scale, the Hospital Anxiety and Depression Scale, the Visual Analogue Scale for pain, the Brief Coping Orientation to Problem Experienced and the Functional Assessment of Cancer Therapy Scale – General Measure. Workers and single patients with higher education level showed a worse QoL. Moreover, anxiety and pain were negatively associated with QoL, while spirituality and 'Instrumental Support' coping style were positively associated with QoL. In the Italian sample, it was observed that when patients are close to death, faith is a more important component of spirituality than meaning/peace. This study confirms that QoL could be related to physical and psychological symptoms, and this reiterates the importance of faith in end‐of‐life care.